What Drives the Employment of Public-private Partnerships in Kazakhstan and Russia: Value for Money? - Mouraviev, Nikolai (Organizations and Markets in Emerging Economies, 2012)
Public-private partnerships (PPPs) are employed in many countries as an alternative method of public service provision in which partners from the public and private sectors share their resources, responsibilities, and risks. Some well-justified factors that drive the partnership development are value for money and lack of budget funding. As PPP drivers may be unique, thepaper surveys the reasons for PPP expansion in two transitional countries, Kazakhstan and Russia. Based on detailed discussion of the commonly employed reasons for partnering (such as greater value for money, or lower total social cost associated with a PPP as opposed to contracting out a service), internal and external PPP drivers in Kazakhstan and Russia have been categorized and examined. Among internal drivers, the need to attract private initiative and funding for upgrading the utilities and housing infrastructure is most influential because of enormity of the task for which governments lack resources. The countries’ intention to align themselves with the requirements of perceived international best practices is yet additional influential driver of external nature. The paper concludes that public policy in the two countries is the major driving force for PPP development although the value for money concept and transaction cost economics appear to be neglected. The emerging PPP policy paradigm in Kazakhstan and Russia has facilitated PPP development in recent years, since 2005. However, lack of reliable solutions and instruments for PPP formation and implementation significantly slows down PPP expansion.